Die Geschichte der Shoah im virtuellen Raum Eine Quellenkritik - Bothe, Alina (Europäisch-jüdische Studien - Beiträge, 2019)
Researching and remembering the history of the Shoah has shifted to the digital media. This study analyzes the implications and consequences of this digital turn. Using the concept of virtual spaces of remembrance, it formulates an original theoretical approach. The work focuses on the Visual History Archive, the most important digital archive of testimonials by survivors of the Shoah.